Engaging school personnel in making schools safe for girls in Botswana, Malawi, and Mozambique. (January 2016) - Schwandt, Hilary M.; Underwood, Carol
Highlights: School environments can contribute to girls' vulnerability to HIV. We test an intervention with teachers to create safe school environments for girls. In Botswana, girl learners report a reduction in teachers asking for sex. Abstract: Girls are vulnerable to HIV in part because the social systems in which they live have failed to protect them. This study evaluates a program aimed at making schools safe for girl learners in order to reduce girls' vulnerability to HIV in Botswana, Malawi, and Mozambique. In addition to an extensive process evaluation with school personnel program participants, program facilitators, and community members, a cross-sectional post-intervention survey was conducted among adolescent girls in the three countries. The total sample size was 1249 adolescent girls (ages 11–18). Bivariate and multilevel, multivariate analyses were conducted to assess the association between school participation in the intervention and a decrease in teachers offering sex in exchange for academic favors. In Botswana, girls who attended an intervention school, as compared to girls who attended a non-intervention school, were significantly more likely to report a reduction in teachers offering sex in exchange for favors. Communication interventions that both challenge and empower school personnel to create safer environments for schoolgirls can have positive effects, particularly in settings with sufficient resources to support change.